HUBUNGAN SUBTIPE MOLEKULER KARSINOMA MAMMAE DENGAN LOKASI METASTASIS DI RSPAD GATOT SOEBROTO JAKARTA TAHUN 2020 - 2022 - Alisya Putri Salsabila, (2023)
Introduction: Breast cancer is the most common cancer and the leading cause of death in women. One of the main causes of death from breast cancer is metastases to vital organs. Metastasis is the migration of the primary tumor and is followed by genomic instability in tumor cells. Hematogenous spread of the primary tumor resulting in metastases to vital organs such as bones, lungs, liver and brain. Purpose: This study aims to determine the relationship between the molecular subtype of mammary carcinoma and the location of metastases at the Gatot Soebroto Army Hospital in 2020 - 2022. Methods: This study used a cross-sectional observational analytic design based on secondary data in the form of medical records. Retrieval of medical record data taken by total sampling. The statistical analysis used was the chi-square test and the multinomial logistic regression test. Results: The total sample of the study that met the research criteria was 144 samples. The results showed that the molecular subtype Luminal A had a tendency to occur in liver metastases (41.4%), Luminal B had a tendency to occur in bone metastases (47.9%), HER2+ had a tendency to metastases in the lungs (42.9%) , and Triple-Negative has a tendency to occur metastases in the brain (47.8%). The results of multivariate analysis showed that luminal molecular subtypes were 14 times more at risk of developing bone metastases, while non-luminal molecular subtypes were 14 times more at risk of developing metastases in the brain. Conclusion: There is a significant relationship between the molecular subtypes of mammary carcinoma and the location of the metastases (p-value = 0.000). Molecular subtypes of mammary carcinoma are associated with metastatic patterns based on the interaction of receptors and ligands produced by tumor cells. Keywords: Mammary Carcinoma, Location of Metastases, Molecular Subtype